Developing a Gagne theory-based learning video for thematic subject in elementary school - Putra, I Gede Widiartana; Warpala, I Wayan Sukra; Sudatha, I Gde Wawan; Utami, Ni Putu Rara Stianing (International research journal of management, IT and social sciences, 2022)
The COVID-19 has shown many significant impacts in life such as in educational field which required students and teachers to conduct a blended learning using creative learning media. It should be able to make the students learning independently. However, that was not an easy thing since the teacher only used a conventional learning media: lecturing and textbook. To solve it, this research aimed to design learning media which focused on Tematic Subjects from Indonesian curicculum of 2013. The development was focused on Science subject only. The development model used ADDIE model and implemented Gagne's 9 steps/events of learning theory. The results of the research found that (1) design of Science learning video with the ADDIE model, (2) Science learning video is valid with resulted: good predicate (80.4%) on expert review of the subject matters, very good predicate (97, 7%) on expert review of the Science learning video media, very good predicate (94.1%) on learning design expert review, very good predicate (93.76%) on individual test, very good predicate (92.61%) on small group test, and very good predicate (90.45%) on field test. Importantly, (3) the effectiveness of development concluded that there was a significant difference between the results of pretest and posttest.